Changes in tobacco-related morbidity and mortality in French women: worrying trends. (11th November 2019) - Olié, Valérie; Pasquereau, Anne; Assogba, Frank A G; Arwidson, Pierre; Nguyen-Thanh, Viet; Chatignoux, Edouard; Gabet, Amélie; Delmas, Marie-Christine; Bonaldi, Christophe
Abstract: Background: The high prevalence of smoking among French women since the 1970s has been reflected over the past decade by a strong impact on the health of women. This paper describes age and gender differences in France of the impact of smoking on morbidity and mortality trends since the 2000s. Methods: Smoking prevalence trends were based on estimates from national surveys from 1974 to 2017. Lung cancer incidence were estimated from 2002–12 cancer registry data. Morbidity data for chronic obstructive pulmonary disease (COPD) exacerbation and myocardial infarction were assessed through hospital admissions data, 2002–15. For each disease, number of deaths between 2000 and 2014 came from the national database on medical causes of death. The tobacco-attributable mortality (all causes) was obtained using a population-attributable fraction methodology. Results: The incidence of lung cancer and COPD increased by 72% and 100%, respectively, among women between 2002 and 2015. For myocardial infarction before the age of 65, the incidence increased by 50% between 2002 and 2015 in women vs. 16% in men and the highest increase was observed in women of 45–64-year-olds. Mortality from lung cancer and COPD increased by 71% and 3%, respectively, among women. The estimated number of women who died as a result of smoking has more than doubled between 2000 and 2014 (7% vs. 3% of all deaths). Conclusions: The increase in the prevalence of smoking among women has a major impact on the morbidity and mortality of tobacco-related diseases in women and will continue to increase for a number of years.